Personal Resources, Emergency Remote Teaching, Burnout and Workaholism among Teachers - Letícia Scandiani Soave; Clarissa Pinto Pizarro de Freitas; Leonardo Fernandes Martins (Paidéia (Ribeirão Preto))
Abstract: Although the changes in the organization of the work of teaching during the Covid-19 pandemic have been well documented, little is known about their impact over time. This study aimed to understand the relationship between remote emergency teaching, personal resources and consequent outcomes among teachers, assessed by psychometric scales of occupational self-efficacy, meaningful work, psychological flexibility, burnout and work addiction. There were 111 primary and secondary school teachers from the state of Rio de Janeiro who took part of this study. Using structural equations, it was identified that ERT acted as a risk factor for workaholism, while personal resources such as occupational self-efficacy, meaningful work and psychological flexibility proved to be protective against burnout. The results highlight the importance of policies to support teachers, aimed at promoting personal resources alongside other actions aimed at mitigating adverse effects in periods of crisis.